The Definition of Green Public Procurement in Lithuanian Legal Regulation - Rudauskienė, Rimantė (Teisė, 2019)
[full article and abstract in Lithuanian; abstract in English] The article focuses on the analysis of definition of green public procurement and its consolidation in Lithuanian legal regulation, revealing the legal basis for green procurement, examining and comparing definition of green procurement in terms of legislative and sub-legislative legal regulation, considering the application of sub-legislative definition of green procurement and its subsequent legal regulation in practice, identifying the main shortcomings of such regulation, proposing solutions for its improvement. Summary Green public procurement in Lithuania is regulated at the legislative and sub-legislative level: the law establishes general rules for the application of environmental protection requirements, which provides for legal possibilities for contracting authorities to implement environmental protection requirements in the course of public procurement; sub-legislative regulation specifies a specific definition of green procurement by pre-setting environmental protection requirements for specific green products which remain unchanged during the particular procurement, accurately defining their content and implementation conditions. The legal bases for green procurement reveal ambiguity in the perception and definition of it, highlight issues with environmental content. It is suggested to relinquish the regulation of environmental protection requirements exclusively in the context of legal regulation of public procurement and consolidate an interdisciplinary approach to green procurement, viewing it as a measure which balances economic and environmental interests. Also, the establishment of the main environmental objectives and requirements, applicable to green procurement, would be welcome. The definition of green procurement, permissible under the law, allows for a broad and extensive concept and is characterized by a procedural nature and unclear content of environmental protection requirements. However, the definition of green procurement, enshrined in the sub-statutory regulation and used in practice, only partially implements the legislative provisions of legal regulation. Moreover, the legislative provisions are implemented very specifically and in great detail, covering only a limited scope of environmental protection requirements. Environmental protection requirements of a more general nature, permissible under the law, are rarely foreseen in the narrow definition. Therefore, the definition of green procurement, which would not be limited to requirements for green products, but would allow taking into consideration sufficient legal possibilities, concerned with environmental requirements, would satisfy the best integration of environmental protection requirements into the legal regulation of public procurement. If a narrow definition of green public procurement with significant drawbacks continues to dominate in Lithuania, there is a danger that green procurement will remain a formal instrument. It is suggested to strengthen contract enforcement and control, as well as encourage more frequent use of advanced environmental criteria, gradually moving to the exclusive implementation of these criteria. The new possibilities for the inclusion of environmental aspects into public procurement at both EU and national levels are not well implemented in the sub-legislative definition of green public procurement and its subsequent legal regulation in Lithuania. It is suggested to improve the sub-legislative regulation of green procurement accordingly by considering new environmental provisions in the public procurement regulation, implementing them in relevant environmental protection requirements.